2002
DOI: 10.1054/jhsb.2002.0843
|View full text |Cite
|
Sign up to set email alerts
|

Simple Curettage without Bone Grafting for Enchondromata of the Hand: With Special Reference to Replacement of the Cortical Window

Abstract: We studied 23 patients (25 bones) with enchondromata of the hand which were treated with simple curettage without bone grafting. The cortical window was replaced in 18 bones (group A), whereas it was not replaced in six bones (group B). In one bone, only half of the cortical window was replaced. Local recurrence was not seen in any patient. Although bone grafting was not performed, new bone formation was observed in all the patients. Radiographic and functional results were excellent in most bones. Restoration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 20 publications
2
34
0
6
Order By: Relevance
“…However, the technique of bone grafting involves operative harvest from a donor site having several complications, including painful scar, infection, hematoma, fracture, and gait disturbances (16). Therefore, several investigators proposed treatment of benign bone tumors by simple curettage without bone grafts and reported promising results (17)(18)(19)(20). In the current study, using a minimally invasive arthroscopic excision technique without bone grafting, most patients had eventual relief of symptoms and pain with four excellent, two good and one satisfactory wrist Mayo function result.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technique of bone grafting involves operative harvest from a donor site having several complications, including painful scar, infection, hematoma, fracture, and gait disturbances (16). Therefore, several investigators proposed treatment of benign bone tumors by simple curettage without bone grafts and reported promising results (17)(18)(19)(20). In the current study, using a minimally invasive arthroscopic excision technique without bone grafting, most patients had eventual relief of symptoms and pain with four excellent, two good and one satisfactory wrist Mayo function result.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of solitary enchondroma, some authors have recommended simple curettage without bone grafting and have reported good clinical results, especially in younger patients. However, such patients must undergo casting and wait for 4 to 6 weeks before they can resume unrestricted daily activity, and some patients experience joint contracture of the affected limb [7,16,17]. Autologous bone grafting is performed conventionally, but the contribution of cancellous bone to the structural strength in the short term is considered to be very low [9].…”
Section: Discussionmentioning
confidence: 99%
“…The most common site for this lesion is the proximal phalanx, [2] followed by the metacarpals [5]. A thorough review of the literature suggests that the fifth finger is the most commonly involved in the hand with an incidence of 30-34.2% [6,7]. There has been no sex predilection for these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The exact rate of recurrence of these tumors is difficult to gauge due to the recurrent lesions being asymptomatic [9]. Sassoon et al and Gaulke et al reported a recurrence rate of 7 and 14.3% respectively [7,9]. Tao et al in his study of 20 cases reported a recurrence rate of 5% [9].…”
Section: Introductionmentioning
confidence: 99%